2020
DOI: 10.1017/s0031182020000165
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish plague affects juvenile survival and adult behaviour of invasive signal crayfish

Abstract: The spread of invasive, non-native species is a key threat to biodiversity. Parasites can play a significant role by influencing their invasive host's survival or behaviour, which can subsequently alter invasion dynamics. The North American signal crayfish (Pacifastacus leniusculus) is a known carrier of Aphanomyces astaci, an oomycete pathogen that is the causative agent of crayfish plague and fatal to European crayfish species, whereas North American species are considered to be largely resistant. There is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Emerging wildlife diseases usually occur due to movement of pathogens or ecosystem alterations of either anthropogenic or natural origin, and may threaten local biodiversity (Cunningham et al, 2012;Daszak et al, 2000;Schmeller et al, 2020). In the case of successful invaders like the signal crayfish, such diseases may also affect invasion success and even alleviate its negative effects on the ecosystem (Fincham et al, 2019;Thomas et al, 2020). In this study, we recorded the extensive manifestation of histopathological lesions in hepatopancreas of the majority of examined signal crayfish individuals along its entire invasion range in the Korana River.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging wildlife diseases usually occur due to movement of pathogens or ecosystem alterations of either anthropogenic or natural origin, and may threaten local biodiversity (Cunningham et al, 2012;Daszak et al, 2000;Schmeller et al, 2020). In the case of successful invaders like the signal crayfish, such diseases may also affect invasion success and even alleviate its negative effects on the ecosystem (Fincham et al, 2019;Thomas et al, 2020). In this study, we recorded the extensive manifestation of histopathological lesions in hepatopancreas of the majority of examined signal crayfish individuals along its entire invasion range in the Korana River.…”
Section: Discussionmentioning
confidence: 99%
“…However, susceptible crayfish and A. astaci seemed to have created a novel and complex relationship, with evidence for a rapid co-evolution of native crayfish and A. astaci (Jussila et al, 2015(Jussila et al, , 2021a. Moreover, the alien crayfish in their newly invaded biogeographic regions in Europe show increased susceptibility with even population collapses reported (e.g., Jussila et al, 2014a;Sandström et al, 2014;Thomas et al, 2020). As a result, among crayfish stocks in Europe, the resistance of both native European and alien crayfish against the crayfish plague has changed, as has the virulence of the disease agent A. astaci (e.g., Jussila et al, 2015).…”
Section: On the Brink Of Extinction: Crayfish Plague Is Wiping Out Native Crayfish Stocksmentioning
confidence: 99%
“…Laboratory scale infection studies have revealed significant virulence differences among and within A. astaci haplogroups and even the existence of very low virulent strains (e.g., Makkonen et al, 2012;Jussila et al, 2017;Francesconi et al, 2021). The invasive crayfish, especially P. leniusculus, have lately been shown to be susceptible to A. astaci, which points to the high virulence of the infecting A. astaci haplogroup B and possibly a lowered resistance of P. leniusculus toward A. astaci (Aydin et al, 2014;Jussila et al, 2014a;Thomas et al, 2020). Laboratory experiments have demonstrated that the A. astaci of haplogroup B, although highly virulent, is also capable of exhibiting a significant but narrow range of virulence variation (Jussila et al, 2013a).…”
Section: On the Brink Of Extinction: Crayfish Plague Is Wiping Out Native Crayfish Stocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Crayfish (Decapoda: Astacidea) are a diverse taxonomic group of freshwater crustaceans (Crandall & De Grave 2017; Taylor et al . 2019), containing both critically endangered endemic species (Taylor et al . 2007; Crandall & Buhay 2008; Bláha et al .…”
Section: Introductionmentioning
confidence: 99%